B Breeding practice and use of medicinal plants against gastrointestinal parasites of small ruminants by the Bwa community in Burkina Faso : Breeding practice and use of medicinal plants against gastrointestinal parasites of small ruminants by the Bwa community in Burkina Faso - TIANHOUN, Denté Fidèle; MEDA, Nãg-Tiéro Roland; KONATE, Almamy; KABORE, Adama; TAMBOURA, H. Hamidou; BELEM, Adrien Marie Gaston (International Journal of Phytomedicine, 2025)
The rearing of small ruminants is widespread in Burkina Faso and is an important source of income for communities. The present study carried out is a contribution to the knowledge of local knowledge and to the valuation of the recipes of the traditional veterinary pharmacopoeia. The aim of the study was to identify the farming practices of small ruminants in the Bwa community and to identify the traditional remedies used against gastrointestinal parasites. It took the form of semi-structured interviews with 121 randomly selected breeders from the community. The results obtained showed that breeders have a good perception of animal pathologies, in particular gastrointestinal strongyloses (31.1%) and, faced with these, 26.45% resort to medicinal plants with an anthelmintic effect. A total of 32 recipes formulated from medicinal plants have been identified, the most used plants of which are Combretum micranthum G. Don (12.5%) and Sarcocephalus latifolius (Sm.) Bruce (12.5%). The main reasons given for the adoption of traditional veterinary medicine were the effectiveness of traditional remedies (40.6%), the high cost of modern drugs (28.1%) and the absence of a veterinary agent at the right time. (18.7%). For a development of these means of management of gastrointestinal parasitosis by the Bwa community, studies to evaluate the anthelmintic efficacy and toxicity tests are necessary.